FORMING ANALYSIS OF COMPOSITE AND FIBRE-METAL LAMINATE SYSTEMS - Sivakumar, Dhar Malingam (2012)
This study examines the stamp forming methodology for manufacturing thermoplastic composites and fibre-metal laminates consisting of thermoplastic composites. A finite element model was developed to elucidate the forming of domes. Experimental work was carried out by stamping these domes in an open die configuration. A real time strain measurement system was used to capture the strain evolution during forming. It was found that there is a good correlation between the numerical and experimental values of strain during forming thus validating the finite element simulations. It was found that that stamp forming is indeed a viable technique for mass production of body panels made of composite materials.